Health system costs of skin cancer and cost-effectiveness of skin cancer prevention and screening. Issue 2 (March 2015) - Gordon, Louisa G.; Rowell, David
<x xml:space="preserve">Abstract</x> The objective of this study was to review the literature for malignant melanoma, basal and squamous cell carcinomas to understand: (a) national estimates of the direct health system costs of skin cancer and (b) the cost-effectiveness of interventions for skin cancer prevention or early detection. A systematic review was performed using Medline, Cochrane Library and the National Health Service Economic Evaluation Databases as well as a manual search of reference lists to identify relevant studies up to 31 August 2013. A narrative synthesis approach was used to summarize the data. National cost estimates were adjusted for country-specific inflation and presented in 2013 euros. The CHEERS statement was used to assess the quality of the economic evaluation studies. Sixteen studies reporting national estimates of skin cancer costs and 11 cost-effectiveness studies on skin cancer prevention or early detection were identified. Relative to the size of their respective populations, the annual direct health system costs for skin cancer were highest for Australia, New Zealand, Sweden and Denmark (2013 euros). Skin cancer prevention initiatives are highly cost-effective and may also be cost-saving. Melanoma early detection programmes aimed at high-risk individuals may also be cost-effective; however, updated analyses are needed. There is a significant cost burden of skin cancer for many countries and health expenditure for this disease will grow as incidence increases. Public investment in skin cancer prevention and early detection programmes show strong potential for health and economic benefits.